Development of Attendance Management System: an Experience - Siti Hawa, Apandi; Rozlina, Mohamed (2013)
Class teacher need to take students’ daily attendance for every school days and analyze of attendance data. It is hassle for teacher to make analysis of attendance data manually and ensure no error prone in that pro-cess. This study proposes to develop a web based application, Attendance Management System (AMS) to solve this problem. This system is part of SMA (Sekolah Menengah Agama) Management System and is implementing in Pahang religious schools under supervision of Jabatan Agama Islam Pa-hang (JAIP). This system includes functions for class teacher to record stu-dent attendance, Guru Penolong Kanan (GPK) to generate school attendance report and the discipline teacher to view truancy statistics. The result shows that this system can help the school management to manage the student attendance.